2012
DOI: 10.3892/mmr.2015.3554
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the oncogenic function of distal-less 4 by microRNA-122 in hepatocellular carcinoma

Abstract: Abstract. Distal-less 4 (DLX4) is a member of the DLX family of homeobox genes. Recent reports have suggested that abnormal expression of DLX4 is present in several types of human tumors, including breast cancer, leukemia and colon cancer. However, the function and the mechanistic regulation of DLX4 in hepatocellular carcinoma (HCC) are elusive. In the present study, a proportion of hepatocellular carcinomas were identified to exhibit upregulated DLX4 expression. This study proposed that the overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, our investigation did not find the association between DLX4 methylation and BP1 expression in CML patients, which indicated that other mechanism might also be involved in the regulation of BP1 expression. Xie et al demonstrated that down-regulation of DLX4 in hepatocellular carcinoma cell lines was regulated by microRNA-122 through binding to its 3 0 untranslated region [31]. Further studies are needed to determine the other potential mechanism in the regulation of DLX4 expression.…”
Section: Discussionmentioning
confidence: 97%
“…However, our investigation did not find the association between DLX4 methylation and BP1 expression in CML patients, which indicated that other mechanism might also be involved in the regulation of BP1 expression. Xie et al demonstrated that down-regulation of DLX4 in hepatocellular carcinoma cell lines was regulated by microRNA-122 through binding to its 3 0 untranslated region [31]. Further studies are needed to determine the other potential mechanism in the regulation of DLX4 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence has demonstrated that numerous miRNAs present ectopic expression in HCC patient serum and plasma as well as in HCC cells and tissues; thereby, miRNAs may be useful as novel clinical markers for the early diagnosis, therapeutic monitoring and prognostic prediction of HCC [ 13 ]. For example, miR-122, which is highly abundant in liver, was significantly down-regulated in a large number of HCC patients, ultimately suppressing tumor invasion, proliferation and metastasis in HCC by directly binding to the 3′-UTR of the Distal-less 4 (DLX4) gene [ 14 ]; miR-21, which is markedly up-regulated in HCC, could promote tumor invasion and metastasis and accelerate tumor growth by targeting phosphatase and tensin homolog (PTEN) and programmed cell death 4 (PDCD4) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xu Q et al reported that overexpression of miR-122 repressed proliferation but induced apoptosis by targeting pyruvate kinase muscle 2 (PKM2) in HCC 72 . Another report found that miR-122 could downregulate the expression of oncogenic distal-less 4 (DLX4), knockdown the expression of this oncogene would inhibit HCC cells proliferation 73 . Overexpression of miR-137 was reported to reduce HepG2 cells proliferation by targeting EZH2 76 .…”
Section: Mirnas and Proliferation And Apoptosis Of Hccmentioning
confidence: 99%